Las visitas domiciliarias femeninas en Colombia. Del trabajo voluntario a su profesionalización - Castro Carvajal, Beatriz (Sociedad y Economía, 2008)
The model of household visits was established in Colombia in the second half of the nineteenth century. Women began to participate in a regular way from the beginning of the twenty century through the creation of associations. This was the entrance to voluntary work for women. Afterwards, this work becomes professional through the creation of the first social work schools in Colombia. This paper aims at illustrating this process